Perbandingan Efektivitas Teknik Menyikat Gigi Kombinasi Horizontal–Vertikal dan Fone’s–Vertikal terhadap Status Kebersihan Gigi dan Mulut Anak - Lisnayetti Lisnayetti; Dewi Rosmalia; Nova Herawati; Nabila Nanda Yoza (Poltekkes Kemenkes Padang, 2026)
Tooth brushing is the primary method for controlling dental plaque. The horizontal–vertical combination technique and the fone’s-vertical technique are simple methods commonly used by children in daily life. This study aimed to analyze the differences in dental and oral hygiene status among 12-year-old children using these techniques at SDN 16 Kampeh and SDN 15 Simarasok, Agam Regency. This study employed a quasi-experimental design with a pretest–posttest approach. A total of 48 respondents were selected using a saturated sampling technique. Data were collected through the Hygiene Index examination. Data analysis included univariate and bivariate analyses using the independent t-test. The results showed that the improvement in dental and oral hygiene was 22.58% for the horizontal–vertical combination technique and 34.62% for the fone’s-vertical technique, with a p-value of 0.000 (p ≤ 0.05). In conclusion, the fone’s-vertical technique is more effective in improving dental and oral hygiene compared to the horizontal–vertical combination technique.